Hukum Keluarga Kontemporer dalam Sistem Perundang-Undangan di Indonesia: Perspektif Pluralisme dan Pembaruan Hukum - Alkaizha Nuran Hakiki; Siah Khisyi’ah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. Contemporary family law in Indonesia has undergone significant transformation due to social change, technological advancement, and increasing awareness of human rights and gender equality. This study aims to analyze the development of contemporary family law within the Indonesian legal system from the perspectives of legal pluralism and legal reform. Employing a normative juridical approach with descriptive-analytical methods, this research examines primary legal materials, including statutory regulations, court decisions, and secondary legal literature. The findings indicate that Indonesian family law reflects a pluralistic legal system integrating state law, Islamic law, and customary law. The interaction among these legal systems has generated various contemporary legal issues, including child marriage, interfaith marriage, domestic violence, children's rights, reproductive technology, gender equality, and legal protection for vulnerable family members. Furthermore, judicial decisions of the Constitutional Court and the Supreme Court have played a significant role in developing new legal norms that promote justice and legal certainty. Nevertheless, challenges remain regarding legal harmonization, gender inequality, and inconsistencies in legal implementation. Therefore, comprehensive family law reform is required to establish a more inclusive, responsive, and justice-oriented legal system capable of addressing contemporary societal developments. Contemporary Family Law; Legal Pluralism; Legal Reform; Gender Equality; Indonesian Legal System.